Examining the Effectiveness of Folktale in Enhancing Students’ Listening Comprehension on Narrative Story - Tri Ilma (Department of Indonesian Language Education, Graduate School, University of Muhammadiyah Prof. DR. HAMKA, 2020)
Listening does not receive special attention in teaching and learning processes of English at the Eleventh Grade of MAN 8 Jakarta. This is caused by English teacher’s misconception that speaking and writing should be put in the first priority because they are considered as productive skills. Meanwhile, listening is classified into respective skill. In teacher’s view, productive skills is often valued batter than receptive skill. Consequently, some students do not have good listening comprehension. In principal, this study was conducted to examine the effectiveness of folktale in enhancing students’ listening comprehension on narrative story. Moreover, due to this study utilized experimental method, so two classes were involved. They were XI IPA 1 acted as experimental group and XI IPA II acted as control group. In addition, to obtain valid data, sixty students from both groups were selected randomly to join pre-test and post-test with similar listening test items. The findings of this study showed that the mean score of post-test for experimental group was 80.8 and 68.53 for control group with the degree of freedom (df) was 58. However, the value of t0 (t-count) was 5.96 and the value of tt (t-table) on degree of significance of 5% was 1.67. Having obtained the data, the researcher compared t0 to tt and the result showed that t0 > tt =5.96 > 1.67. It indicates that that H1 or alternative hypothesis was accepted. In other words, This study pointed out that there was significant effect of folktale in enhancing students’ listening comprehension on narrative story.